Two new species and two new records of myxomycetes from subtropical forests in China - Gao, Yang; Yan, Shu-Zhen; Wang, Gao-Wei; Chen, Shuang-Lin (Phytotaxa, 2018)
Two new myxomycetes from subtropical forests of China, Arcyria aeruginosa sp. nov. and Diderma subochraceum sp. nov., are described and illustrated. Arcyria aeruginosa occurred on rotten stem of bamboo and differs from all known species of the genus in having dense spines on inner surface of cups. The diagnostic feature of D. subochraceum is single-layered peridium which dehisces by longitudinal or stellate slit. Preliminary phylogenetic analyses based on partial 18S rDNA sequences support the establishment of the two new species. Additionally, Didymium saturnus H.W. Keller and Fuligo luteonitens L.G. Krieglst. & Nowotny are reported from China for the first time.